Mucoepidermoid Carcinoma of Palate-Diagnostic Challenges - R S Sathawane; R N Mody; A R Parate (Wolters Kluwer Medknow Publications, 2004)
A 32 years old male reported with pain and swelling in left maxillary region of face since 2 months and painless palatal swelling on left side since 1 year Radiographic features were mimicking a fibro osseous lesion, while CT scan was suggestive of central hemangioma. First FNAC revealed acinic cell carcinoma, whereas repeated FNAC revealed Mucoepidermoid Carcinoma. From postoperative histopathological studies, a final diagnosis of mucoepidermold carcinoma was confirmed. Mucoepidermoid carcinoma is an unusual type of major salivary gland tumor particularly affecting parotid glands; primarily occurs in 3rd to 5th decades of life. Mucoepidermoid carcinoma of minor salivary gland is rare and mostly affects palate. Histologically there are three variants of mucoepidermoid carcinoma. 1) Low grade mucoepidermold carcinoma 2) Intermediate grade mucoepidermold carcinoma 3) High grade mucoepidermold carcinoma. A diagnostically challengeable rare case of "Intermediate Grade Mucoepidermoid Carcinoma" affecting palatal minor salivary gland is presented.